2008
DOI: 10.2170/physiolsci.rp001508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation of the Superior Ovarian Nerve and the Ovarian Plexus Nerve on the Ovarian Estradiol Secretion Rate in Rats

Abstract: Abstract:The present experiments examined the effects of electrical stimulation of the superior ovarian nerve (SON) and the ovarian plexus nerve (OPN) on the ovarian estradiol secretion in rats. The rats were anesthetized on the day of estrus, and the ovarian venous blood was collected intermittently. The secretion rate of estradiol from the ovary was calculated from differences in the estradiol concentration between ovarian venous plasma and systemic arterial blood plasma, and from the flow rate of ovarian ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
(35 reference statements)
4
30
1
Order By: Relevance
“…Owing to this blood sampling procedure, changes in ovarian venous estradiol concentration during nerve stimulation would not affect estradiol concentration in systemic arterial plasma. We confirmed the stability of estradiol concentration in systemic arterial plasma between samples collected both at the beginning and at the end of experiment [7]. When the nerve was not stimulated, the ovarian venous plasma flow rate, the ovarian venous estradiol concentration, and the estradiol secretion rate from the ovary were all stable when compared between 5 samples for 35 min [7].…”
Section: Methodssupporting
confidence: 72%
See 4 more Smart Citations
“…Owing to this blood sampling procedure, changes in ovarian venous estradiol concentration during nerve stimulation would not affect estradiol concentration in systemic arterial plasma. We confirmed the stability of estradiol concentration in systemic arterial plasma between samples collected both at the beginning and at the end of experiment [7]. When the nerve was not stimulated, the ovarian venous plasma flow rate, the ovarian venous estradiol concentration, and the estradiol secretion rate from the ovary were all stable when compared between 5 samples for 35 min [7].…”
Section: Methodssupporting
confidence: 72%
“…Our previous study showed that superior ovarian nerve stimulation decreased both plasma flow rate of ovarian venous blood (ovarian blood flow) and ovarian estradiol secretion rate in anesthetized rats [7]. Our present study demonstrated that these two events induced by stimulation of the superior ovarian nerve stimulation were caused by the activation of different alpha adrenoceptors subtypes.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations